2008
DOI: 10.1038/sj.sc.3102150
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and profile of spinal tuberculosis in patients at the only public hospital admitting such patients in KwaZulu-Natal

Abstract: Study Design: A retrospective chart review at the major provincial public hospital serving patients with spinal injuries/pathology. Objectives and setting: To determine the incidence of spinal tuberculosis (Tb) and establish the profile of these patients treated at King George V Hospital (KGV) in KwaZulu-Natal, South Africa. Methods: A total of 525 medical records for the period March 2005 to April 2006 were reviewed. Data from 104 files of Tb spine cases were categorized according to demographic details, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 6 publications
10
26
0
1
Order By: Relevance
“…Previous reports [5,12] have indicated the thoracic region to be the most affected area in the vertebral column, followed by the lumbar region. These findings are similar to those found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports [5,12] have indicated the thoracic region to be the most affected area in the vertebral column, followed by the lumbar region. These findings are similar to those found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological deficits such as weakness, numbness, gait difficulties, and incontinence occurred less frequently [4]. Godlwana et al [5] reported that 56% of their subjects presented with neurological deficits, in which 24% had complete paraplegia and 32% incomplete paraplegia. McLain et al [6] reported that neurological deficits are common with long-standing thoracic and cervical involvement, and if untreated, neurological involvement may progress to complete and incomplete paraplegia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertebral location is the most common form of skeletal tuberculosis [7][8][9]. Osteoarticular tuberculosis (OAT) is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal tuberculosis remains a frequent disease in developing countries [7][8][9][10]. Vertebral location is the most common form of skeletal tuberculosis [7][8][9].…”
Section: Discussionmentioning
confidence: 99%